(3OjhGf cTGLes - (3cTGLe , eMehO Hf GdMSjf Hf GdSfOj Hf TGgc, CHh GdaJM,J (B360 (3g` s
(3ChdgG (B:s
(3bGd CHhGdaJM eMehO GdSfOj bGd aj MQa GdgeRI HcGA hbd YfGA GdHcGA Ydi QRA PQjI GdCfHjGA dFf Pd ajg YRjR GdOehY dbO YR aj Pdjd GdYRGA s
(3BNQgG (B:s
(3JKjQ JQGH eUQYg HbQf CLe cCfg HYV GdedGhj HGLRY efc jhe jbhd Ndj Caj GdYfGhjf CfJ hCfJ KGhj s
(3GdOjhGf eQJH Ydi MQha GdgLGAs
(3hQOJ CjVkG JMJ Qbe (B2191(3, (B2202(3, (B2185s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B43 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B159s
Keywords: (3GdCOHs